¿Qué pueden aportar a los enseñantes los diferentes enfoques de la didáctica de las matemáticas? (segunda parte) - Brousseau, Guy (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
In the first part of this paper we raised the question of whether a customized theory of the didactics of mathematics was legitimate and presented and overview of such a theory. This second part analyses the contribution from and constraints to the classical approaches and social practices on which they rely, and discusses the relationship between mathematics and its didactics.